Gavilán caracolero (rostrhamus sociabilis) como controlador biológico del caracol manzana (pomacea canaliculata) en cultivos de arroz del sitio Puerto Loor - Andrade Macías, Yomaly Melissa (2021)
The main objective of this research was to determine the potential of the snail hawk (Rostrhamus sociabilis) as a biological controller of the apple snail (Pomacea canaliculata) in rice crops at the Puerto Loor site. In this sense, analyzing the rice production process in 25 plots, the foraging behavior of the bird was determined, to later establish its potential as a biological controller. Said behavior was determined in two specimens, female and male, which on the day of monitoring recorded 53 and 59 foraging cycles respectively, these cycles were made up of four categories, search for food, management of the prey in flight, management of the perch prey and search for the next food, in each category the time invested by the two birds was counted and the respective comparison was subsequently made. In addition to this, the feeding of R. sociabilis was monitored for four weeks, showing that this bird in its adult phase fed on 790 snails at this time with a consumption density of 184 snails / week * ha and a potential of 88.04 %, said result exceeded the potential stipulated for the Aramus guarauna (11.96%), demonstrating that the snail hawk has excellent potential as a biological controller of the apple snail